A direct aspiration first pass technique with the new ARC catheter for thrombectomy of large vessel occlusion strokes: A multicenter study. Issue 2 (April 2019) - De Marini, Pierre; Nayak, Sanjeev; Zhu, François; Bracard, Serge; Anxionnat, René; Tonnelet, Romain; Liao, Liang; Richard, Sébastien; Humbertjean, Lisa; Mione, Gioia; Lacour, Jean-Christophe; Derelle, Anne-Laure; et al.
Background and purpose: A direct aspiration first pass technique involves first-line aspiration to remove the thrombus through a large-bore aspiration catheter in large vessel strokes. The aim of this study was to assess safety and clinical outcomes with a direct aspiration first pass technique using the new ARC catheter. Methods: A retrospective analysis of prospectively collected data from three university hospitals was performed between June 2016 and May 2018. The following parameters of all acute ischemic stroke interventions using the ARC catheter were analyzed: use of intravenous thrombolysis, National Institutes of Health Stroke Scale scores at presentation and discharge, successful reperfusion (modified Thrombolysis in Cerebral Infarction 2b–3), procedure duration, procedure-related complications and 90-day clinical outcome (modified Rankin Scale score). Results: In total, 41 patients were included in the study and anterior circulation occlusion was noted in 35 (85%). The median National Institutes of Health Stroke Scale at admission was 18 and prior intravenous thrombolysis was administered in 35 patients (85%). Only six (15%) patients required the use of a rescue stent retriever. Successful reperfusion was achieved in 40 patients (98%) with a median procedure time of 32 minutes. No catheter-related complications were observed. Symptomatic intracerebral hemorrhage occurred in one patient (2%). Median National Institutes of Health Stroke Scale at discharge was 3; 49% were independent and 10% died at 90 days. Conclusions: In the present study, the ARC catheter allowed a 98% successful reperfusion rate. The complication rate was in line with those of previous a direct aspiration first pass technique publications.